Effects of nonsurgical periodontal therapy on C-reactive protein and serum lipids in Jordanian adults with advanced periodontitis - Kamil, Wisam Alaa; Habashnah, Rola; Khader, Yousef; Hilal Abbood Al-Bayati, Lina; Taani, D. (John Wiley & Sons, 2011)
Background and Objective: Data on whether periodontal therapy affects serum CRP levels are inconclusive. The aim of this study was to determine if nonsurgical periodontal therapy has any effect on CRP and serum lipid levels in patients with advanced periodontitis. Material and Methods: Thirty-six systemically healthy patients, ‡ 40 years of age and with advanced periodontitis, were recruited for the study. Patients were randomized consecutively to one of two groups: the treatment group (n = 18) or the control group (n = 18). Treated subjects received nonsurgical periodontal therapy, which included oral hygiene instructions and subgingival scaling and root planing. Systemic levels of inflammatory markers [C-reactive protein (CRP) and the lipid profile] were measured at baseline and 3 mo after periodontal therapy. Results: Nonsurgical periodontal therapy in the treatment group resulted in a significant reduction in the serum CRP level. The average CRP level decreased from 2.3 mg/dL at baseline to 1.8 mg/dL (p < 0.005) after 3 mo of periodontal therapy. The average reduction (95% confidence interval) in CRP was 0.498 (95% confidence interval = 0.265–0.731). In the treatment group, the reduction in CRP was significantly, linearly and directly correlated with the reduction in the plaque index, the gingival index and the percentage of sites with pocket depth ‡ 7 mm (Pearson correlation coefficient = 0.746, 0.425 and 0.621, respectively). Nonsurgical periodontal therapy had no effect on the lipid parameters. Conclusion: This study demonstrated that nonsurgical periodontal therapy results in a significant reduction in the serum CRP level. The effect of this outcome on systemic disease is still unknown.